The first experience of coronary artery bypass grafting based on the data of a multispiral computed tomogram of the heart, combiner with simultaneous operations, is the analysis of immediate results - Nikonenko, A. S.; Nikonenko, A. A.; Chmul, K. O.; Osaulenko, V. V.; ErmolaevЕ. V. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Despite the development of diagnosis and treatment methods, coronary heart disease still occupies a leading place in disability and mortality. At present, coronary artery bypass grafting is the main method of treating ischemic heart disease. Selective CAG is a reference study of coronary artery disease, while at the same time, multispiral computed tomography of the coronary arteries continues to evolve as an alternative to invasive CAG. The aim of the study was to evaluate the clinical significance of 64-slice computed tomography of the heart. The data of 34 patients who underwent CABG on the basis of multispiral computed tomography coronary artery data were studied. In our study, the high specificity of the multispiral computed tomography heart method was confirmed, which was 96%.